Effect of Some Biotic and Abiotic Elicitors on Phenolic Acids and Diterpenes Production from Rosemary (Rosmarinus officinalis L.) Leaf and Callus Analyzed by High Performance Liquid Chromatography (Hplc) - Rashid, Khaleel I; Ibrahim, Kadhim M; Hamza, Subhi J (Al-Nahrain Journal of Science, 2018)
The yield of phenolic acids; rosmarinic acid (RA), caffeic acid (CAF) and phenolic diterpenes; carnosic acid (CA), carnosol (CAR), rosmanol (ROL) from rosemary (Rosmarinus officinalis L.) was investigated. Aqueous extraction was conducted for leaf and callus tissues, the chemical analysis for extracts was carried out using high performance liquid chromatography (HPLC). Data showed that RA and CAF production was 4.5, 2.7 µg/ml respectively. CA and CAR production reached 3.3, 2.8 µg/ml when the fungal elicitor; Fusarium oxysporum was added at the concentration 2.0 mg/l (2×104CFU/ml), except ROL which was found at high levels (4.3, 4.2 and 4.6 µg/ml) only from leaf extracts, untreated callus and when callus treated with 0.4 mg/l of CaCl2 respectively.